Going beyond the usual suspects: engaging street artists in policy design and implementation in Bogotá. Issue 3 (3rd July 2022) - DeShazo, Jessica L.
Abstract: This article examines how Bogotá has developed civic engagement with street artists to design and implement a program promoting the responsible practice of graffiti by engaging in a thought experiment. Bogotá used participatory policymaking and public outreach that is carried out by street artists as forms of civic engagement. This article contributes to our understanding of how government officials can engage groups who typically do not participate in the policymaking process. The research reveals there is some effort from the government to build bonds and bridges with the program for the responsible practice of graffiti and the artists. The findings suggest that participatory policymaking and public outreach are useful methods to engage members of the public who are not typically represented in the policymaking process. The article provides key lessons that can be applied to other cities that wish to engage different groups of people who are unrepresented in traditional forms of civic engagement in local government.